RITUAL BELO KAMPUNG PADA MASYARAKAT SUKU ASLI ANAK RAWA DI KAMPUNG PENYENGAT KECAMATAN SUNGAI APIT KABUPATEN SIAK - Mulyana, Intan; ", Risdayati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was conducted in Penyengat Village, Sungai Apit District, Siak Regency. The background of raising this issue is to discuss the Tradition Belo of the Indigenous People of the Swamp Children Village, the Belo Tradition village, which is useful for protecting communities and villages from calamities, and epidemics. This thesis aims to analyze the implementation of the Belo Kampung ritual implementation, as well as knowing the meaning of the tradition of Belo Kampung. This research is a qualitative research with a descriptive approach. The data used are in the form of primary and secondary methods. Data collection techniques were carried out by the method of observation, interviews, and documentation, all of which answered research problems regarding the Tradition Belo Kampung. The research informants were the people of Penyengat Village which consisted of Bomo, Adat Stakeholders, Indigenous People of the Rawa Children, Religious Leaders, Village Heads, Communities who were not native to the Swamp Children. Based on the results of the study, it was found that the implementation of this Tradition consisted of pre-ritual, tradition implementation and post-ritual, which lasted for one day.Keywords: Belo Kampung, Indigenous Children of Swamp, Tradition